One–step Synthesizable Lindqvist−isopolyoxometalates as Promising New Catalysts for Selective Conversion of Glucose as a Model Substrate for Lignocellulosic Biomass to Formic Acid. Issue 11 (26th July 2016) - Albert, Jakob; Mehler, Julian; Tucher, Johannes; Kastner, Katharina; Streb, Carsten
Abstract: A series of Lindqvist‐isopolyoxometalates [M6 O19 ] n− (M=W, V) were synthesized under one‐pot conditions and were applied in the homogeneous oxidation of glucose as a model substrate for lignocellulosic biomass to formic acid (FA), which offers a new field for application of isopolyoxometalates (IPA) in catalysis. Their low molecular weight and facile accessibility in aqueous solution together with their tuneable redox properties offers a new and straightforward path for optimized precious metal free oxidation catalysts. We have systematically synthesized and characterized a series of vanadium‐ and tungsten‐based Lindqvist structures and verified their applicability in the selective oxidation of glucose to FA. Maximum FA‐yields of 39 % in aqueous solution under non‐optimized conditions were observed for Cs4 [V2 W4 O19 ] and it is shown that reactivity and selectivity can be tuned by metal substitution of the cluster: FA formation is favoured with increasing V‐substitution of the [W6 O19 ] 2− ‐framework. Moreover, the influence of different inorganic counter cations was investigated. Abstract : A series of Lindqvist‐isopolyoxometalates [M6 O19 ] n− (M=W, V) were synthesized under one‐pot conditions and were applied in the homogeneous oxidation of glucose as a model substrate for lignocellulosic biomass to formic acid (FA), which offers a new field for application of isopolyoxometalates (IPA) in catalysis.